The Influence of Discipline and Employee Perfomance on the Quality of Public Services at the Department Environment and Waste Management of Ambon City - Tri Hemat Br Manurung; Pieter Sammy Soselisa; Julia Theresia Patty (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the influence of work discipline and employee performance on the quality of public services at the Department of Environmental Affairs and Waste Management of Ambon City. Public service quality reflects the government’s capacity to fulfill community needs and expectations, particularly in waste management services that directly affect environmental cleanliness, public health, and community satisfaction. Methodology: This research employed a quantitative survey approach involving employees directly engaged in waste management services. Data were collected through structured questionnaires using a five-point Likert scale to measure work discipline, employee performance, and public service quality. Instrument validity and reliability were tested prior to analysis. The data were analyzed using descriptive statistics and multiple linear regression, supported by classical assumption tests to ensure the reliability of the regression model. Main Findings: The results show that work discipline has a positive and significant effect on public service quality. Employee performance also has a positive and significant effect. Simultaneously, both variables significantly influence service quality with a strong coefficient of determination. Disciplined behavior and optimal performance substantially improve reliability, responsiveness, assurance, empathy, and tangible aspects of public services. Novelty/Originality of this study: This study provides an integrated quantitative analysis of discipline and performance as simultaneous determinants of service quality in the municipal waste management sector, offering empirical evidence to strengthen citizen-oriented local governance.